End Of the Minister's Legal Status in Palestinian Law - Ahmad Mohammed Hamad (Hang Tuah Law Journal, 2019)
The Palestinian law laid down a set of legal rules regulating the Minister's legal status and his relationship with the career status. In accordance with the Palestinian law, the Minister's legal status shall be established through several stages, procedures and decisions between the initial and another end which has the legal effect in the establishment of this legal status, as well as end of Minister's legal status shall be in the availability of one of the cases stipulated by the Palestinian law, either to be the resignation of the government as a whole or to withhold confidence, resignation or dismissal of the Minister or the vacancy of the ministerial position. In view of the fact that there are no limited cases of the end of the Minister's legal status within a single Palestinian law, the researcher, through the results and recommendations of this research, will attempt to solve this problem by analyzing and explaining some legal legislations and books. Therefore, the study will address the on Minister's legal status in the Palestinian law, considering that this matter has a legal effect on the future application.